2018
DOI: 10.1002/asia.201801645
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom‐doped MoSe2 Nanosheets with Enhanced Hydrogen Evolution Kinetics for Alkaline Water Splitting

Abstract: Electrochemical water splitting for hydrogen generation is a vital part for the prospect of future energy systems, however, the practical utilization relies on the development of highly active and earth‐abundant catalysts to boost the energy conversion efficiency as well as reduce the cost. Molybdenum diselenide (MoSe2) is a promising nonprecious metal‐based electrocatalyst for hydrogen evolution reaction (HER) in acidic media, but it exhibits inferior alkaline HER kinetics in great part due to the sluggish wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…[6][7][8][11][12][13] High affinity of Co to the saturation of the edges of layered d-metal dichalcogenides is well established and is extensively applied in catalysis. [14][15][16] Evidence already showed that homogeneous Co doping is beneficial for the HER in both alkaline and acidic media, [17][18][19][20] since it improves both the hydrogen adsorption free energy and the water adsorption/dissociation capabilities. [17] The remaining question is whether Co doping is more efficient at the edge sites or incorporated as a substituent dopant within the layered crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][11][12][13] High affinity of Co to the saturation of the edges of layered d-metal dichalcogenides is well established and is extensively applied in catalysis. [14][15][16] Evidence already showed that homogeneous Co doping is beneficial for the HER in both alkaline and acidic media, [17][18][19][20] since it improves both the hydrogen adsorption free energy and the water adsorption/dissociation capabilities. [17] The remaining question is whether Co doping is more efficient at the edge sites or incorporated as a substituent dopant within the layered crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…dopants, including Fe, [192] Zn, [197] Ni, [198] N, [199] P, [200] S, [200] etc. While attempts to promote the catalytic efficiency with the doping phase transition method also has been reported failed, for instance, Nb/Ta doped MoS 2 and WS 2 reported by Chua et al [201] Phase transition trials of obtaining T-phased TMD usually ends up in a mixture of these two phases.…”
Section: Tmds Catalystsmentioning
confidence: 99%
“…To address the issues, Mo based materials can be coupled with a conductive carbon matrix to enhance electric conductivity, the dispersion of Mo sites and specific surface area [17,[47][48][49][50]. In addition, doping with heteroatoms effectively improves the intrinsic activity, lowers the kinetic energy barrier for dissociation, facilitates the charge transport and optimizes the H binding energy [26,[51][52][53][54]. Moreover, the construction of heterostructures forms a synergy and benefits the HER performances [34,55].…”
Section: Smart Designs Of Mo Based Her Catalystsmentioning
confidence: 99%
“…Nevertheless, the sluggish reaction kinetics, because of their intrinsically low activity and poor conductivity, limit their large scale applications in HER [23]. To address the issues, various modifications have been developed to improve the catalytic performances of Mo based materials, such as combination with carbon matrix, doping with heteroatoms and construction of heterostructures [24][25][26][27]. So far, most of the reviews are focused on specific Mo based compounds; a comprehensive review based on the modification strategies of Mo based electrocatalysts rather than the materials is rarely reported in HER [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%